The Analysis of Buying and Selling of Goods Without Price Tags in The Perspective of Fiqh Mu’amalah at Student Cooperative Stores of PMDG Campus - Haerul Akmal; Teguh Eka Prasetya; Abdurrahman Azmi (Universitas Islam Lamongan, 2022)
This research aims at finding out the practice of selling goods without price tags and the fiqh mu’amalah review on its sales at student cooperative stores of PMDG Campus. The method used in this research is descriptive qualitative which describes the various conditions, situations and social phenomena that occur. Applying the field research, this study uses the interview results with the management of student and consumer cooperatives, as a source of data collection. Based on this research, sales in student cooperatives apply the same system as in supermarkets, where the consumer takes the items he wants to buy on the storefront, then takes them to the cashier to carry out the transaction process. Since the price tag is not included, the price given by the cashier sometimes changed or unclear. Hence, it can be assumed that the sale of goods without the use of price tags in student cooperatives Store still has a light ghara>r element, which lies in pricing. Due to the absence of a price tag, the management of the student cooperative sometimes speculated on their merchandise, giving rise to ghara>r. However, the ghara>r that occurs does not happen at the core of the trade, and does not cause hostility, so the buying and selling practice in student cooperatives store is legal.